Implementasi Penilaian Keterampilan Kewarganegaraan Berdasarkan Kurikulum 2013 - Magdalena, Ina; Nurchayati, Aan; Anastasia, Anastasia (TSAQOFAH, 2023)
One aspect that made the change and arrangement in curriculum 2013 is the standard of assessment witch tailored to the content standards, competency standards and the process standards. Nonetheless, in the end the arrangement of the assessment focused on learning. Skills assessment requires studant to demonstrate a certain competence. This assessment is intended to determine whether the knowledge has been mastered learners can be used to identify and solve problems in real life. Mastery learning for skills determined by the school, gradually continue to improve the school completeness criteria studied by considering the potential and characteristics of each school as a form of improving the quality of learning outcomes. The approach research is a qualitative research with descriptive methods. These results indicate that, the implementation of the curriculum 2013 there are still many obstacles. This constraint is caused by many factors. The dominant factor is the desire or willingness of teachers in applying the skills assessment system contained in this curriculum. There is still the need for the participation of various stakeholders in the success of the application of the system of assessment of skills in the curriculum 2013. The government should continue to socialize and training in enhancing the competence of teachers on aspects pence judgments of these skills.